Appraisal of Bearing Capacity and Modulus of Subgrade Reaction of Refilled Soils - Arshid, Muhammad Usman; Kamal, M. A. (Salehan Institute of Higher Education, 2020)
Soil is remoulded, replaced, or improved in place to meet the required engineering properties. Relative compaction is the measure of the resulting engineering improvement. But design engineers need the allowable bearing capacity while the modulus of subgrade reaction is the primary input of modern foundation design software. The current research appraised a correlation between Relative Compaction ( ), Moisture Content ( ), and allowable bearing capacity ( ) and another correlation between , RC, MC, and modulus of subgrade reaction ( ). The test samples were extracted from each trial of the standard proctor test using purpose-built extraction tubes. Allowable bearing capacity has been determined by performing unconfined compression tests on the extracted tubes. The relationships have been established employing statistical analysis. It was noticed that soil samples at the lower moisture content (6-9%) show brittle failure before reaching the allowable strain. The soil samples having a moisture content of 10-14% exhibited shear failure, nearly simultaneous to the allowable strain. The soil samples having higher moisture content undergone a strain of 15% without showing the shear failure. A simple equation has also been appraised to determined Ks involving the three-input variable, i.e., , , and . Moderate correlations have been found to exist between the studied parameters, owing to some other variables' influence. Recommendations for future studies have been drawn to quantify the effect of identified parameters.Â Doi: 10.28991/cej-2020-03091606 Full Text: PDF